СИСТЕМНОЕ МЫШЛЕНИЕ В ПОЗНАНИИ - Ниязимбетов, М.К.; Алланазарова, Б.Ж. (SCIENCE and SOCIETY, 2020)
It is clear that the cognition of complex world and changing principals are impossible adequately depict methodology sciences in traditional method, so that it came up necessaty to develop the alternative methods and thinking style of research phenomena. The article is analysed the philosophical aspects of cognition system in complexity of consciousness.
Keywords: complexity; system; nonlinearity; cognitive system; fragment cognition; reduction; holism; system modeling